2018
DOI: 10.1016/j.joca.2018.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Differences in subchondral bone plate and cartilage thickness between women with anterior cruciate ligament reconstructions and uninjured controls

Abstract: This study demonstrates that subchondral bone plate thickness differences are prominent following knee injury, as measured by HR-pQCT, but no statistically significant differences in cartilage morphology, measured by MRI, were found between ACLR knees compared to contralateral and control knees. These data provide novel insight into post-traumatic knee injuries that may be signs of early OA pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 45 publications
(68 reference statements)
0
22
0
Order By: Relevance
“…In the present study, we found that cartilage degeneration is significantly associated with more severe sclerosis changes in STB microarchitecture, which supports the theory of a subchondral bone-cartilage functional unit where the OA disease state could destroy the homeostatic relationship between them under abnormal knee loads. In addition, Bhatla et al [42] showed that subchondral bone changes may be indicative of early OA pathogenesis of post-traumatic knee injuries, and Chen et al [43] also showed that abnormal STB remodeling is earlier than that of cartilage change and may contribute to the early pathogenesis of T2D-associated knee OA. However, given the cross-sectional design of the present study, we cannot prove the sequence of occurrence and causality between cartilage and STB, which requires further research to investigate the role of STB in progression of OA.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that cartilage degeneration is significantly associated with more severe sclerosis changes in STB microarchitecture, which supports the theory of a subchondral bone-cartilage functional unit where the OA disease state could destroy the homeostatic relationship between them under abnormal knee loads. In addition, Bhatla et al [42] showed that subchondral bone changes may be indicative of early OA pathogenesis of post-traumatic knee injuries, and Chen et al [43] also showed that abnormal STB remodeling is earlier than that of cartilage change and may contribute to the early pathogenesis of T2D-associated knee OA. However, given the cross-sectional design of the present study, we cannot prove the sequence of occurrence and causality between cartilage and STB, which requires further research to investigate the role of STB in progression of OA.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported a higher average Tb.N and Tb.Th, which contributed to sclerotic changes in subchondral bone of advanced OA . In fact, the hypothesis that changes in subchondral bone might affect OA development is commonly acknowledged . Radin and Rose had originally proposed that densification of subchondral bone might lead to increased stiffness, thereby introducing adverse stress concentrations and sequential damage to articular cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…(5)(6)(7) In fact, the hypothesis that changes in subchondral bone might affect OA development is commonly acknowledged. (4,9,(33)(34)(35)(36) Radin and Rose (37) had originally proposed that densification of subchondral bone might lead to increased stiffness, thereby introducing adverse stress concentrations and sequential damage to articular cartilage. Clinically, OP is another recognized factor that causes subchondral bone alterations in the functional unit of cartilage and subchondral bone.…”
Section: Discussionmentioning
confidence: 99%
“…Many different approaches have been used to analyze cartilage thickness maps and our approach was based on a two‐step process. First data from the matched control subjects with normal knees were used to determine the side‐to‐side thickness differences and corresponding 95% confidence limits (i.e., normal thickness maps) at each 1 ×1 mm grid location.…”
Section: Discussionmentioning
confidence: 99%
“…If future work supports this hypothesis, our finding of a twofold increase in slope for the combined ACL-LM group in comparison to the isolated ACL group may provide a biomechanical explanation for why the risk of PTOA is greater for those that suffer combined injuries to the ACL and meniscus in comparison to those that suffer isolated ACL trauma. Many different approaches have been used to analyze cartilage thickness maps 9,11,[28][29][30][31][32][33] and our approach was based on a two-step process. First data from the matched control subjects with normal knees were used to determine the side-to-side thickness differences and corresponding 95% confidence limits (i.e., normal thickness maps) at each 1 ×1 mm grid location.…”
mentioning
confidence: 99%